Efficacy of a novel herbal composition licorice flavonoid oil in subject with metabolic syndrome: a randomized double-blind placebo-controlled clinical study - Hosoe, Kazunori; Nakagawa, Kaku; Ueda, Takahiro; Hosoda, Masato; Panda, Sanjib Kumar; Morikawa, Hideyuki; Jha, Sandeep (Functional foods in health and disease, 2017)
Background: In order to evaluate the effects of licorice flavonoid oil (LFO) on waist circumference, blood pressure, lipid profile, body fat composition, body weight, body mass index (BMI), and fasting blood glucose in patients with metabolic syndrome, a 12 week randomized double-blind placebo-controlled study was conducted. Methods: Fifty patients with metabolic syndrome aged between 18-75 years were assigned to either the LFO or placebo group. Abdominal waist circumference, blood pressure, body weight, and BMI were assessed at baseline, week 4, week 8, and week 12. Clinical laboratory examinations, fat composition, and fasting blood glucose level were assessed at baseline (week 0) and final visit (week 12).Results: A total of 50 subjects (25 subjects in each group) completed the 12 week study. Significant changes from baseline were observed in body weight, waist circumference, and BMI in the LFO group compared to the placebo group from week 4 or week 8 onwards. No adverse events were noted throughout the study. Conclusion: The present study suggests that LFO is a promising dietary nutrient for improving metabolic syndrome, particularly through its beneficial effect of reducing body weight, BMI, and possibly the amount of visceral fat. Keywords: licorice flavonoid oil; Glycyrrhiza glabra L.; metabolic syndrome; body mass index